“Desarrollo de una aplicación móvil de vigilancia para la gestión de monitoreo del parqueadero de la Universidad Técnica De Cotopaxi Extensión La Maná”. - Rodríguez Parrales, Cristopher Alberto (2021)
This research project aims to improve security through a video surveillance system for the parking lot of the Technical University of Cotopaxi Extension La Maná, which allows to have a constant monitoring from wherever it is located, in this way it is you will get alert if any anomalies are happening immediately. Mobile devices have become a technological tool very useful for establishing communication from anywhere, these smart devices evolve over time, allowing them to transform to our mobile devices on a surveillance device because they adapt to security applications through a video surveillance system remotely, the purpose of this system is to provide security to the establishment in this way to keep the area safe, the purpose of developing a Mobile surveillance app for parking monitoring management is to perform monitoring and have camera viewing as long as have access to the Internet. The development of the project is based on research, the mobile application was developed on the Android Studio platform and uses Firebase platform as a database. These tools enable effective results, which ensure the fulfilment of the objectives Raised. Finally, the installation of the CCTV system (CCTV) and the application was implemented mobile surveillance for the safety of the vehicles of which the university community makes up, which has an ideal and easy interface to use, this tool is very useful to prevent theft in our university facilities, using new security technologies through video surveillance systems allow for greater security by keeping the area or public or private establishment monitored and monitored from anywhere.